Sensor-network-based mobile home care system - Lu, Haochuan. (2009)
The whole world faces problems of population aging. Having seniors at home alone would make most people worry, as one cannot keep a close eye on them all day. Worse still, medical plans for elderly people are so mass-produced that they cannot deliver e®ective results. The demand for low-cost geriatric care systems is high. This project included work done in the ¯eld of teleoperated mobile robotic home care system. A mobile robot prototype with visual capability and communication capabilities actualized via sensor networks was designed and implemented to realize two functions: real-time health monitoring and telepresence. With the aid of a wireless biosensor, the system can provide solutions for re- mote monitoring of real-time electrocardiogram (ECG) signals. Equipped with a rotatable video camera and a wireless communication device, the robot allows virtual visits for remote parties. It can be guided from any- where with Internet connection and provides live images. Moreover, our system can be applied to act as a mobile surveillance system to secure one's residence. The hardware platform was constructed based on an ARM9-based micro- controller. Peripheral functional modules were built up and integrated to- gether. An embedded real-time software and a PC-based control software, which collaboratively control the home care system and provide live display of video stream, were developed. Testing shows the prototype built in this project possess desired capability and reliability to function properly.